2016
DOI: 10.1080/19443994.2015.1022004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-economic analysis of modular solar still under Algerian climatic conditions: effect of collector and condensation chamber area

Abstract: In this paper, a thermal-economic analysis of a modular solar still was investigated. For that, a modular solar still was designed. The collector area and the condensation chamber area effect on the productivity and distilled water cost were examined. Simulations were performed according to meteorological data of Algiers (Algeria) using Liu Jordan method. Results show that the surface area of collector increase increases the evaporated water and distilled water production at the same time. The average annual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It was found that the evaporated water increases with the increase of solar thermal collector area. It was also found that an increase of the condensation chamber surface, decreases the annual average production of distillate water .…”
Section: Introductionmentioning
confidence: 94%
“…It was found that the evaporated water increases with the increase of solar thermal collector area. It was also found that an increase of the condensation chamber surface, decreases the annual average production of distillate water .…”
Section: Introductionmentioning
confidence: 94%
“…The payback time of 1.23 and 26.58 years was the minimum and maximum time at a selling price of $0.13 and a selling price equal to the production price, respectively. Kerfah et al [71] designed a modular solar still to numerically perform a thermal-economic analysis and investigate the effect of the collector and condensation chamber area on the productivity and the cost of distilled water. They found that increasing the collector area reduces the distilled water cost, while the amount of freshwater reduces by increasing the condensation chamber area.…”
Section: Exergy Analysismentioning
confidence: 99%
“…Moreover, adding the second and third collector leads to 48% and 23% higher productivity in the summer, respectively (Figure 26). Kerfah et al [71] revealed that the increasing collector area leads to higher evaporated water which obtains higher freshwater. They obtained annual freshwater of 482.35 and 2083.65 L for collector areas of 2 and 10 m 2 , respectively (Figure 27).…”
Section: Water Depth (M)mentioning
confidence: 99%
See 1 more Smart Citation
“…the first part consist to improve the evaporation by coupling the basin solar still with flat plate solar collector [1], a solar water heater [2], reflective plates [3], etc. The second part includes the improvement of the condensation by: the cooling of the glazing [4], the addition of a condensation chamber [5][6].…”
Section: Introductionmentioning
confidence: 99%